Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Is there a nice way to see that the series $$\sum_{n=0}^\infty (-1)^n (n+1)/n!$$ converges to $0$? I just did the computation numerically. Thanks

share|improve this question
2  
Hint: compute $\sum_{n=1}^N (-1)^n (n+1)/n!$. To this end, write $\sum_{n=1}^N (-1)^n (n+1)/n!$ as $\sum_{n=1}^N (-1)^n \cdot n/n! + \sum_{n=1}^N (-1)^n \cdot 1/n!$ –  Yury Oct 11 '12 at 23:28
add comment

2 Answers

up vote 4 down vote accepted

$$\eqalign{ & \sum\limits_{n = 0}^\infty {{{( - 1)}^n}} \frac{{n + 1}}{{n!}} = \cr & = \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}n}}{{n!}}} + \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} = \cr & = \sum\limits_{n = 1}^\infty {\frac{{{{( - 1)}^n}}}{{\left( {n - 1} \right)!}}} + \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} = \cr & = \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^{n + 1}}}}{{n!}}} + \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} = - \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} + \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} = 0 \cr} $$

share|improve this answer
    
pretty cool actually) –  Alex Oct 12 '12 at 1:02
add comment

First notice that $$e^{-x}=\sum_{n=0}^\infty \frac{(-1)^nx^n}{n!}.$$ If we multiply this by $x$, we get $$xe^{-x}=\sum_{n=0}^\infty \frac{(-1)^nx^{n+1}}{n!}.$$ Now if we differentiate, we get $$e^{-x}-xe^{-x}=\sum_{n=0}^\infty \frac{(-1)^n (n+1)x^{n}}{n!}.$$ We now set $x=1$ to get $$0=e^{-1}-e^{-1}=\sum_{n=0}^\infty \frac{(-1)^n (n+1)}{n!}.$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.